Integration of accounting recognition in the implementation of the Occupational Health and Safety Management System (GEON Journal (Management, Organizations and Business), 2020)
The implementation of management systems has led employers to develop administrative processes, under the premise of regulatory compliance, to avoid sanctions or fines, activities that were previously carried out on an eventual or informal basis, according to customer needs, situations that have given relevance to the budget analyzes within the planning processes of the companies, allowing them an economic balance. Conditions that founded the approach of an analysis with a quantitative approach of the accounting recognition for the design, implementation and improvement of the management system in occupational health and safety in 150 companies in the commerce sector of the El Estero neighborhood, in Villavicencio. This process began with the characterization of the companies by regime, to continue with the analysis of the definition of the investment items, the accounting processes and finally determine the decision-making process of senior management according to the development of management versus occupational risks. This results suggest the strengthening and integration of financial planning in the occupational health and safety management system during the implementation process of the strategic and operational activities of the PDCA cycle (Plan, Do, Check, Act), in order to avoid the loss of resources and establish this management as an ally in the continuous improvement of the company, of working conditions, an added value for its clients and a competitive advantage in the market.
Keywords: Planning; Accounting; Financial Management; Job safety; J8 labor standards; M48 Government policy and regulation; M41 Accounting; M54 Labor management